A Proposed Framework to Enhance Pharmaceutical Distribution Companies Using Data Mining Techniques. - Abdel-Fattah, Manal A.; Ouf, Shimaa; Ali, Esraa Ahmed (International Journal of Supply Chain Management, 2021)
This paper discusses the challenges that meet pharmaceutical distribution companies and how to overcome it by using data mining techniques, these challenges are out of stock in the inventory that caused many problems and losses to the company, excessive inventory can also lead to damaged, expired items resulting from this lose a lot of money, So pharmaceuticals distribution companies must control their inventory levels to prevent costs of excessive inventory also prevent losing customers. And to solve these problems we need to implement data mining techniques to improve the retail supply chain process in pharmaceutical distribution companies. The paper proposes a framework to improve the retail supply chain process in pharmaceutical distribution companies starting from forecasting the products of the next month ending with delivering the right amount of medicine to the right place at the right time, in addition, to following up the stock during the month through dashboards.Â